Disproportional ownership structures and corporate R&D investment: from the investor protection perspective. (2nd March 2023) - Zhou, Yu; Zhu, Hongzhang; Hu, Xinyu; Chang, Xiaoxi
Disproportional ownership structures are promised to stimulate innovation. However, very few studies have empirically examined this relationship and compared the dual-class equity structure and stock pyramid structure, two forms of disproportional ownership structures. In this research, from the investor protection perspective by integrating 'contract' and 'legal' perspectives, we explored the impact of disproportional ownership structures on firms' R&D. Using data consisting of Chinese firms with disproportional ownership structures from 2008 to 2018, we found that compared with pyramidal firms, dual-class firms engaged in more R&D investments. We also found that ownership-control rights divergence negatively moderated the dual-class equity structure and R&D investment relationship, while equity restriction further weakened this moderating effect.